2023
DOI: 10.26599/jac.2023.9220728
|View full text |Cite
|
Sign up to set email alerts
|

Tunable polarization-drived superior energy storage performance in PbZrO 3 thin films

Abstract: Antiferroelectric PbZrO3 films have great potential to be used as the energy storage dielectrics due to the unique electric field-induced phase transition character. But the phase transition process always accompanies polarization hysteresis effect that induces large energy loss and lowers Journal of Advanced Ceramics https://mc03.manuscriptcentral.com/jacer 2 the breakdown strength, leading to inferior energy storage density as well as low efficiency. In this work, the synergistical strategies by doping small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Hao et al found excellent energy storage property in PLZST films, followed by much more work including PBLZS, PZO, and PCZ . It has been proved that elemental modification is an efficient strategy for the enhancement of electrical and polarization properties. The recoverable energy storage density ( W reco ), loss density ( W loss ), and total energy density ( W total ), as well as the energy conversion efficiency (η) can be calculated according to eqs - W normalr normale normalc normalo = P normalr P max E .25em normald P W normalt normalo normalt normala normall = 0 P max E .25em normald P η = W r e c o W normalr normale normalc normalo + W normall normalo normals normals × 100 % = W r e c o W t o t a l × 100 % where P max is the maximum polarization intensity of films, and P r is the remnant polarization intensity. In recent years, research related to the energy storage behavior has been focused on the phase transition properties regarding the energy storage scenes. ,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hao et al found excellent energy storage property in PLZST films, followed by much more work including PBLZS, PZO, and PCZ . It has been proved that elemental modification is an efficient strategy for the enhancement of electrical and polarization properties. The recoverable energy storage density ( W reco ), loss density ( W loss ), and total energy density ( W total ), as well as the energy conversion efficiency (η) can be calculated according to eqs - W normalr normale normalc normalo = P normalr P max E .25em normald P W normalt normalo normalt normala normall = 0 P max E .25em normald P η = W r e c o W normalr normale normalc normalo + W normall normalo normals normals × 100 % = W r e c o W t o t a l × 100 % where P max is the maximum polarization intensity of films, and P r is the remnant polarization intensity. In recent years, research related to the energy storage behavior has been focused on the phase transition properties regarding the energy storage scenes. ,…”
Section: Introductionmentioning
confidence: 99%
“…Hao et al found excellent energy storage property in PLZST films, followed by much more work including PBLZS, PZO, and PCZ . It has been proved that elemental modification is an efficient strategy for the enhancement of electrical and polarization properties. The recoverable energy storage density ( W reco ), loss density ( W loss ), and total energy density ( W total ), as well as the energy conversion efficiency (η) can be calculated according to eqs - where P max is the maximum polarization intensity of films, and P r is the remnant polarization intensity. In recent years, research related to the energy storage behavior has been focused on the phase transition properties regarding the energy storage scenes. , It has been reported that high energy density could be obtained due to their large spontaneous polarization and electrode modulation. , However, a narrow working range is still a problem for real application scenes .…”
Section: Introductionmentioning
confidence: 99%
“…Providing advanced dielectric materials with high energy storage properties is critical for the development of dielectric capacitors. [5][6][7] The energy storage performances can be calculated from the polarization-electric field (P-E) loops, as shown in Fig. S1 (ESI †).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many efforts have been put forward to enhance the W rec and Z of PbZrO 3 -based antiferroelectric films, including ionic doping, multilayer structure, nanocrystalline engineering, preparation process, etc. [24][25][26][27][28] For example, the electric fieldinduced phase transition behavior of antiferroelectric thin films can be effectively controlled through doping moderate La 3+ . 29 A W rec of 23.1 J cm À3 and a Z of 73% are obtained in La-doped PbZrO 3 films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation